Impact of mode instability on polarization extinction ratio in backward pumped fiber amplifiers - Shu, Qiang; Zhang, Chun; Li, Fang; Chu, Qiuhui; Guo, Chao; Li, Fengyun; Zhang, Haoyu; Tao, Rumao; Lin, Honghuan; Wang, Jianjun (Frontiers in Physics, 2025)
The influence of mode instability (MI) on polarization extinction ratio (PER) has been investigated in a 2 kW level polarization-maintained (PM) fiber laser system with backward pumping configuration, and the phenomena is different from the existing observations in forward-pumped PM fiber amplifiers. No decrease in PER was noted with the onset of MI, revealing that the MI effect has little impact on PER in backward-pumped PM fiber amplifiers. The discrepancy induced by the pump configuration has been theoretically analyzed, which is attributed to the longitudinal-distribution difference of high order modes induced by the MI effect.